Exploration of the association between the single-nucleotide polymorphism of co-stimulatory system and rheumatoid arthritis - Chen, Ding-Ping; Wen, Ying-Hao; Lin, Wei-Tzu; Hsu, Fang-Ping; Yu, Kuang-Hui (Frontiers in Immunology, 2023)
Introduction The human leukocyte antigen (HLA) has been linked to the majority of autoimmune diseases (ADs). However, non-HLA genes may be risk factors for ADs. A number of genes encoding proteins involved in regulating T-cell and B-cell function have been identified as rheumatoid arthritis (RA) susceptibility genes. Methods In this study, we investigated the association between RA and single-nucleotide polymorphisms (SNPs) of co-stimulatory or co-inhibitory molecules in 124 RA cases and 100 healthy controls without immune-related diseases [including tumor necrosis factor superfamily member 4 (TNFSF4), CD28, cytotoxic T-lymphocyte–associated protein 4 (CTLA4), and programmed cell death protein 1 (PDCD1)]. Results The results showed that there were 13 SNPs associated with RA, including rs181758110 of TNFSF4 (CC vs. CT, p = 0.038); rs3181096 of CD28 (TT vs. CC + CT, p = 0.035; CC vs. TT, p = 0.047); rs11571315 (TT vs. CT, p = 0.045), rs733618 (CC vs. TT + CT, p = 0.043), rs4553808 (AA vs. AG vs. GG, p = 0.035), rs11571316 (GG vs. AG vs. AA, p = 0.048; GG vs. AG + AA, p = 0.026; GG vs. AG, p = 0.014), rs16840252 (CC vs. CT vs. TT, p = 0.007; CC vs. CT, p = 0.011), rs5742909 (CC vs. CT vs. TT, p = 0.040), and rs11571319 of CTLA4 (GG vs. AG vs. AA, p < 0.001; GG vs. AG + AA, p = 0.048; AA vs. GG + AG, p = 0.001; GG vs. AA, p = 0.008; GG vs. AG, p ≤ 0.001); and rs10204525 (TT vs. CT + CC, p = 0.024; TT vs. CT, p = 0.021), rs2227982 (AA vs. GG, p = 0.047), rs36084323 (TT vs. CT vs. CC, p = 0.022; TT vs. CT + CC, p = 0.013; CC vs. TT + CT, p = 0.048; TT vs. CC, p = 0.008), and rs5839828 of PDCD1 (DEL vs. DEL/G vs. GG, p = 0.014; DEL vs. DEL/G + GG, p = 0.014; GG vs. DEL + DEL/G, p = 0.025; DEL vs. GG, p = 0.007). Discussion Consequently, these SNPs may play an important role in immune regulation, and further research into the role of these SNPs of immune regulatory genes in the pathogenesis of RA is required.